Massive Loss of DNA Methylation in Nitrogen-, but Not in Phosphorus-Deficient Zea mays Roots Is Poorly Correlated With Gene Expression Differences - Mager, Svenja; Ludewig, Uwe (Frontiers in Plant Science, 2018)
DNA methylation in plants plays a role in transposon silencing, genome stability and gene expression regulation. Environmental factors alter the methylation pattern of DNA and recently nutrient stresses, such as phosphate starvation, were shown to alter DNA methylation. Furthermore, DNA methylation had been frequently addressed in plants with notably small genomes that are poor in transposons. Here, we compare part of the DNA methylome of nitrogen- and phosphorus-deficient maize roots by reduced representation sequencing and analyze their relationship with gene expression under prolonged stresses. Tremendous DNA methylation loss was encountered in maize under nitrogen-deficiency, but much less with phosphorus-deficiency. This occurred only in the symmetrical cytosine context, predominantly in CG context, but also in the CHG context. In contrast to other plants, differential methylation in the more flexible CHH context was essentially absent. In both deficiency conditions a similar number of differentially expressed genes were found and differentially methylated regions (DMRs) were predominantly identified in transposable elements (TEs). A minor fraction of such DMRs was associated with altered gene expression of nearby genes. Interestingly, although these TEs were mostly hypomethylated, they were associated with both up- or down regulated gene expression. Our results suggest a different methylome regulation in maize compared to rice and Arabidopsis upon nutrient deficiencies and point to highly nutrient- and species-specific dynamics of genomic DNA methylation.